One case of Actinotignum schaalii-induced repeated infections at periumbilical scar accompanied by abscess formation and literature review - Cheng Li; Lili Yang; Min Xu; Tao Zhou; Junning He; Yijie Yin; Yongfang Liu (BMC Infectious Diseases)
Abstract To enhance the current clinical understanding and improve the diagnosis and treatment of Actinotignum schaalii infections, we have presented here a report of the case of recurrent infections at a periumbilical scar, induced by Actinotignum schaalii and complicated by abscess formation in a 50-year-old woman with persistent festering at the site of a periumbilical scar after laparoscopy 9 years ago, with subsequent ruptures over the past 2 years. Physical examination revealed a radial fold scar with localized redness and slight swelling of the skin below the navel. Although no significant increase in the local skin temperature was noted, tenderness was present. A rupture at the site was also observed, and gentle compression produced a small amount of odorless and yellowish viscous pus. Anerobic culturing of the pus for 3 days revealed gray-white, non-hemolytic, spore-free, gram-positive, slightly curved rod-shaped bacteria. These bacteria were identified as A. schaalii using matrix-assisted laser desorption ionization time-of-flight mass spectrometry. The patient was subsequently treated with a 1-month course of oral amoxicillin, combined with debridement and drainage. Her condition improved with regular dressing changes. However, during follow-up 6-month later, the patient presented with a recurrence of the local infection at the scar site, again accompanied by abscess formation and rupture. Notably, the wound size was smaller, and after a 1-week treatment with silver ion, without any systemic antibiotic administration, her condition improved. Next, triamcinolone acetonide combined with lidocaine was injected into the scar three times. No further local infections were observed at the scar site during the subsequent 12-month follow-up.